Status of the Multidrug Resistance-1 Gene of Plasmodium falciparum in Four Malaria Epidemiological Strata, Two Decades after the Abolition of Chloroquine as First-Line Treatment for Uncomplicated Malaria in Cameroon - David Denis Sofeu-Feugaing; Fabrice Nkengeh Ajonglefac; Marcel Nyuylam Moyeh; Tobias Obejum Apinjoh; Marianne Elodie Essende; Gilchrist Destin Talla Kouam; Stephen Mbigha Ghogomu (Journal of Tropical Medicine)
Drug-resistant malaria parasites pose a threat to global malaria control efforts, and it is important to know the extent of these drug-resistant mutations in each region to determine appropriate control measures. Chloroquine (CQ) was widely used in Cameroon for decades, but its declining clinical efficacy due to resistance prompted health authorities in 2004 to resort to artemisinin-based combination therapy (ACT) as the first-line treatment for uncomplicated malaria. Despite numerous efforts to control malaria, it persists, and the emergence and spread of resistance to ACTs make the development of new drugs or the possible reintroduction of discontinued drugs increasingly urgent. Malaria-positive blood samples were collected from 798 patients on Whatman filter paper to determine the status of resistance to CQ. DNA was extracted by boiling in Chelex and analysis of Plasmodium species. Four hundred P. falciparum monoinfected samples, 100 per study area, were amplified by nested PCR, and allele-specific restriction analysis of Pfmdr1 gene molecular markers was performed. Fragments were analyzed using a 3% ethidium bromide-stained agarose gel. P. falciparum was the most abundant Plasmodium species, accounting for 87.21% of P. falciparum monoinfections only. No infection with P. vivax was detected. The majority of samples contained the wild type for all 3 SNPs evaluated on the Pfmdr1 gene with N86, Y184, and D1246 accounting for 45.50%, 40.00%, and 70.00%, respectively. The most abundant haplotype observed was the Y184D1246 double wild type at 43.70%. The results suggest that P. falciparum is the major infecting species and that P. falciparum species with the susceptible genotype are gradually recapturing the parasite population.